Top five unanswered questions in plant cell surface research - Wout Boerjan; Vincent Burlat; Daniel J. Cosgrove; Christophe Dunand; Paul Dupree; Kalina T. Haas; Gwyneth Ingram; Elisabeth Jamet; Debra Mohnen; Steven Moussu; Alexis Peaucelle; Staffan Persson; et al. (The Cell Surface, 2024)
Plant cell wall researchers were asked their view on what the major unanswered questions are in their field. This article summarises the feedback that was received from them in five questions. In this issue you can find equivalent syntheses for researchers working on bacterial, unicellular parasite and fungal systems.